Community-informed, integrated, and coordinated care through a community-level model: A narrative synthesis on community hubs. Issue 2 (March 2022) - Manis, Derek R.; Bielska, Iwona A.; Cimek, Kelly; Costa, Andrew P.
We identify the core services included in a community hub model of care to improve the understanding of this model for health leaders, decision-makers in community-based organizations, and primary healthcare clinicians. We searched Medline, PubMed, CINAHL, Scopus, Web of Science, and Google from 2000 to 2020 to synthesize original research on community hubs. Eighteen sources were assessed for quality and narratively synthesized (n = 18). Our analysis found 4 streams related to the service delivery in a community hub model of care: (1) Chronic disease management; (2) mental health and addictions; (3) family and reproductive health; and (4) seniors. The specific services within these streams were dependent upon the needs of the community, as a community hub model of care responds and adapts to evolving needs. Our findings inform the work of health leaders tasked with implementing system-level transformations towards community-informed models of care.